A Novel Function for the Streptococcus pneumoniae Aminopeptidase N: Inhibition of T Cell Effector Function through Regulation of TCR Signaling - Blevins, Lance K.; Parsonage, Derek; Oliver, Melissa B.; Domzalski, Elizabeth; Swords, W. Edward; Alexander-Miller, Martha A. (Frontiers in Immunology, 2017)
Streptococcus pneumoniae (Spn) causes a variety of disease states including fatal bacterial pneumonia. Our previous finding that introduction of Spn into an animal with ongoing influenza virus infection resulted in a CD8+ T cell population with reduced effector function gave rise to the possibility of direct regulation by pneumococcal components. Here we show that treatment of effector T cells with lysate derived from Spn resulted in inhibition of IFNγ and TNFα production as well as of cytolytic granule release. Spn aminopeptidase N (PepN) was identified as the inhibitory bacterial component and surprisingly, this property was independent of the peptidase activity found in this family of proteins. Inhibitory activity was associated with reduced activation of ZAP-70, ERK1/2, JNK, and p38, demonstrating the ability of PepN to negatively regulate TCR signaling at multiple points in the cascade. These results reveal a novel immune regulatory function for a bacterial aminopeptidase.